Turning a polystyrene microsphere into a multimode light source by laser irradiation - Liu Shimei; Tie Shaolong; Chen Jingdong; Li Guangcan; Yang Jiaxin; Lan Sheng (Nanophotonics)
Polystyrene (PS) is generally considered as a passive optical material that is transparent to light with wavelengths longer than 300 nm. In practice, PS micro- and nanospheres with uniform sizes are usually used to build photonic crystals based on self-assembly mechanism. Here, we demonstrate experimentally that PS microspheres supporting whispery gallery modes can be transformed into multimode light sources by laser irradiation. We show that a PS microsphere placed on a silica substrate can be lighted up when it is consecutively irradiated by using a 488-nm continuous wave laser beam with a pumping power above a threshold. Broadband luminescence emitted from the PS microsphere increases rapidly to a maximum value and decreases gradually with increasing irradiation time, implying the generation and degradation of a certain luminescent material upon laser irradiation. However, the PS microsphere is found to be damaged by high temperature based on morphology examination. By replacing the silica substrate with a thin silver film, the threshold laser power for lighting up a PS microsphere is dramatically reduced. More importantly, we can see enhanced luminescence intensities from the whispery gallery modes supported by the PS microsphere, which becomes an efficient multimode light source. Interestingly, the threshold laser power can be further lowered by inserting a molybdenum disulfide monolayer in between the PS microsphere and the silver film. As a result, the PS microsphere remains nearly unchanged except the formation of the luminescence material. Our findings open a new horizon for the interaction of polymer with laser light by exploiting the optical resonances supported by micro- and nanoparticles and pave the way for constructing photonic devices based on laser-induced luminescent materials in polymers.